2021
DOI: 10.1177/14680874211007232
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of wall heat transfer due to spray combustion in a high-pressure/high-temperature vessel

Abstract: Combustion chamber wall heat transfer is a major contributor to efficiency losses in diesel engines. In this context, thermal swing materials (adapting to the surrounding gas temperature) have been pinpointed as a promising mitigative solution. In this study, experiments are carried out in a high-pressure/high-temperature vessel to (a) characterise the wall heat transfer process ensuing from wall impingement of a combusting fuel spray, and (b) evaluate insulative improvements provided by a coating that promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This, however, requires that the gas temperature is not significantly affected by the change in heat loss due to the coating; the constant h assumption arises from an incomplete understanding of coating roughness effects. 9,[28][29][30][31]33,62 Figure 1 shows a comparison of the fully coupled baseline (uncoated) case to the fully coupled coated case, and the uncoupled coated results. The data are for a steady-state cycle of the production John Deere 4045 engine.…”
Section: Baseline Gas Temperature Assumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, however, requires that the gas temperature is not significantly affected by the change in heat loss due to the coating; the constant h assumption arises from an incomplete understanding of coating roughness effects. 9,[28][29][30][31]33,62 Figure 1 shows a comparison of the fully coupled baseline (uncoated) case to the fully coupled coated case, and the uncoupled coated results. The data are for a steady-state cycle of the production John Deere 4045 engine.…”
Section: Baseline Gas Temperature Assumptionmentioning
confidence: 99%
“…This, however, requires that the gas temperature is not significantly affected by the change in heat loss due to the coating; the constant h assumption arises from an incomplete understanding of coating roughness effects. 9,2831,33,62…”
Section: Uncoupled Thermo-mechanical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Splitter et al 4 analyze the effect on soot production of using EGR and late intake valve closing in a single-cylinder SI high compression ratio engine and conclude that depending on the fuel characteristics (gasoline or LPG), combustion efficiency may be significantly improved when compared to a conventional Diesel engine. Keskinen et al 5 measured heat fluxes in an engine-relevant environment to determine if the use of thermo-swing coating materials helps significantly reduce heat transfer losses. However, they concluded that it is rather difficult to improve the thermal efficiency of the engine by these means.…”
Section: Special Issue: Thiesel 2020 Conference On Thermo-and Fluid-dynamic Processes In Direct Injection Enginesmentioning
confidence: 99%
“…Recently, in view of demands for reductions in carbon dioxide emissions, improvements in thermal efficiency as well as establishment of ultralow emissions in diesel engines are attracting attention and many papers related to the thermal efficiency of diesel engines have been reported in the recent 4 years. The papers can be classified into three categories, including papers on the cooling loss reduction with suppression of heat transfer to the combustion chamber wall, [1][2][3][4][5][6][7][8][9][10][11] applications including the Miller cycle and cylinder deactivation, [12][13][14][15][16] and combustion improvement with optimizations of combustion chamber shapes and fuel injection strategies. 1, Among the fuel injection strategies, highly distributed fuel sprays with increases in the number of nozzle holes as well as with higher fuel injection pressures and smaller nozzle hole diameters are being developed to establish improvements in diesel combustion.…”
Section: Introductionmentioning
confidence: 99%